2009
DOI: 10.1002/anie.200902137
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry on a Cluster Surface: Fixation/Complexation of Potassium and Ammonium Ions with Crown‐Ether‐Like Rings

Abstract: Integrated but separate: A strongly nucleophilic cluster surface allows the selective complexation and separation of ammonium and potassium ions. Six {Mo4VKO6} rings with crown‐ether‐like functionality (see picture; Mo blue, V green, K pink, O red) present in the holes of the investigated cluster complex integrate six ammonium ions (N orange, H yellow).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The first region corresponds to the entrance of the channel and second region corresponds to three lateral cavities, which were reported as the more reactive towards electrofiles. Müller and coworkers and we recently verified these predictions 38…”
Section: Structure Of Cations and Water Inside And Outside Polyoxosupporting
confidence: 73%
“…The first region corresponds to the entrance of the channel and second region corresponds to three lateral cavities, which were reported as the more reactive towards electrofiles. Müller and coworkers and we recently verified these predictions 38…”
Section: Structure Of Cations and Water Inside And Outside Polyoxosupporting
confidence: 73%
“…This distribution of the cations is fully consistent with the location of with K + and NH 4 + ions determined by means of a new X-ray diffraction experiment [24]. Indeed, it was possible to show that the two crown-ether type pores and the functional groups of the three external cavities/holes of Mo 57 V 6 interacted specifically with K + and NH 4 + ions.…”
Section: Cation Distribution Determined By Molecular Dynamics Simulatsupporting
confidence: 63%
“…We discovered a remarkable separation/selective complexation 0020-1693/$ -see front matter Ó 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.ica.2010.07.019 process of these cations on the surface of Mo 57 V 6 , which was unprecedented in inorganic supramolecular chemistry and in ion-pairing research [24].…”
Section: Introductionmentioning
confidence: 99%
“…Extending the molecular dynamic simulation to giant POM macroanions would be very complicated and attractive 14. [H 3 Mo 57 V 6 (NO) 6 O 183 (H 2 O) 18 ] 21– is a nano‐sized anionic cluster and when the counterions are NH 4 + and K + , the compound, (NH 4 ) 11 K 10 [H 3 Mo 57 V 6 (NO) 6 O 183 (H 2 O) 18 ]⋅65H 2 O, has cavities that can accommodate a few counterions (see Figure 7).…”
Section: A Retrospective Summary On the Interaction Between Poms Amentioning
confidence: 99%
“…Assuming all the counter‐cations being Li + , MD simulation showed that all the Li + were found to stay preferably above the two first‐type pores and in the area of the four terminal oxygen atoms (Figure 9). 14…”
Section: A Retrospective Summary On the Interaction Between Poms Amentioning
confidence: 99%